Candidate photoferroic absorber materials for thin-film solar cells from naturally occurring minerals: enargite, stephanite, and bournonite. Issue 6 (6th July 2017) - Wallace, Suzanne K.; Svane, Katrine L.; Huhn, William P.; Zhu, Tong; Mitzi, David B.; Blum, Volker; Walsh, Aron
Abstract : A search for photoactive ferroelectric minerals reveals three candidates, which are investigated using first-principles materials modelling. Abstract : To build on the success of other mineral systems employed in solar cells, including kesterites (Cu2 ZnSnS4 ) and herzenbergite (SnS), as well as mineral-inspired systems such as lead halide perovskites (CH3 NH3 PbI3 ), we have searched for photoactive minerals with the additional constraint that a polar crystal structure is adopted. Macroscopic electric fields provide a driving force to separate electrons and holes in semiconductor devices, while spontaneous lattice polarisation in polar semiconductors can facilitate microscopic photo-carrier separation to enhance carrier stability and lifetimes. We identify enargite (Cu3 AsS4 ), stephanite (Ag5 SbS4 ), and bournonite (CuPbSbS3 ) as candidate materials and explore their chemical bonding and physical properties using a first-principles quantum mechanical approach.